Camus' "Guest": The Inadmissible Complicity - James W. Greenlee (Studies in 20th & 21st Century Literature, 1978)
Early analyses of Camus' tale, "The Guest," generally reflect the political tensions that rent Algeria in the 1950's. Since these tensions have disappeared, we are able to read the tale as a personal drama recounting the moral dilemma of its, narrator-protagonist. Scrutiny of his censored account reveals his retreat from an action which would compromise his innocence. The story registers the author's awareness of the ambiguities of moral decision and testifies to the refinement of his thought since the composition of The Plague.
Keywords: Albert Camus; L& #x27; Hôte; The Guest; morality; complicity